Pengaruh Lingkungan Kerja Dan Gaya Kepemimpinan Terhadap Kinerja Pegawai Melalui Kepuasan Kerja Pada Kantor Wilayah Kementerian Agama Provinsi Sulawesi Barat - Duriah; Djabar, Sadly Abdul; Muin, Sri Adrianti (Jurnal Online Manajemen ELPEI, 2025)
This study aims to determine and analyze the influence of the work environment, leadership style through job satisfaction at the Regional Office of the Ministry of Religious Affairs of West Sulawesi Province. The research approach used in this study is a quantitative method with an explanatory approach. From the total population data, the Slovin formula is used to obtain a sample of 131 respondents. The analysis conducted is Outer Model Analysis consisting of Convergent Validity test, Discriminant Validity test, Composite Reliability test, Average Variance Extracted (AVE) value and Inner Model Analysis consisting of R Square test, Q Square, Direct and Indirect Influence Test and hypothesis test by looking at T and P Values. This analysis uses Partial Least Square (PLS) using SmarthPLS 3.0 software. Based on the analysis results, the Work Environment does not have a significant effect on Employee Performance (0.383 > 0.05), the Work Environment has a positive and significant effect on Job Satisfaction (0.000 < 0.05), Leadership Style has a positive and significant effect on Employee Performance (0.013 < 0.05), Leadership Style has a positive and significant effect on Job Satisfaction (0.000 < 0.05), Job Satisfaction has a positive but not significant effect on Employee Performance (0.019> 0.05), the Work Environment does not have a positive and not significant effect on Employee Performance if through job satisfaction (0.051> 0.05), Leadership Style has a positive and significant effect on Employee Performance if through Job Satisfaction (0.028 > 0.05).